La significatividad anímica del trabajo: una lectura psicoanalítica del valor del trabajo en la constitución del sujeto (2015)
The purpose of this paper is to propose a discussion about de animic meaning of work,this is the value and the main focus of work in the constitution of the subject and the construction of the subjectivityFor this, its going to be based in such (arguicion) on the theorical development of phsycoanalysis, in special ,what is stated by Freud(1930) in respect of his text "El malestar en la Cultura". To make this ,a characterization its going to be developed , of the new realities of work that showcase ever more the value of woek in the pcicological dynamicIcertidumbre ,unsecurity , unestability , etc)After this it is going to be showcased the value of work in the animic activity from the develoments of freud and finally , some of the reflection are going to be staded , developed by the psycodynamic of workaround the relation subject-work